Diplomasi Publik Korea Selatan Dalam Membina Hubungan Bilateral Dengan Korea Utara Tahun 2017-2020 - Asi, Felicia Tarida; Maliki, Musa; Nathanael, Garcia Krisnando (Universitas Komputer Indonesia, 2023)
This study discusses public diplomacy efforts undertaken by South Korea with the aim of reconciliation and fostering good bilateral relations with North Korea during the 2017 – 2020 period. To answer the problem formulation, the writer uses the concept of public diplomacy and multitrack diplomacy. The author uses a qualitative-descriptive research method and conducts a literature study on official government documents as a data collection technique. The results showed that there were three types of public diplomacy activities carried out by South Korea against North Korea during the 2017 – 2020 period. First, sports diplomacy efforts carried out by South Korea to North Korea were carried out through the holding of the 2018 Winter Olympics, the formation of a joint demonstration team taekwondo, organizing inter-Korean basketball matches, and establishing a joint Korean sports team for international matches. Second, the cultural diplomacy efforts carried out were the holding of the “Spring is Coming” concert and the excavation of the Manwoldae historical site. Third, the distribution of humanitarian aid is a public diplomacy effort that is often carried out by South Korea to North Korea. Keywords— Bilateral Relations, North Korea, Public Diplomacy, South Korea